2022
DOI: 10.1038/s41598-022-09491-4
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in molecular structure of alkali activated slag with various water to binder ratios under accelerated carbonation

Abstract: Carbonation of alkali activated materials is one of the main deteriorations affecting their durability. However, current understanding of the structural alteration of these materials exposed to an environment inducing carbonation at the nano/micro scale remains limited. This study examined the evolution of phase assemblages of alkali activated slag mortars subjected to accelerated carbonation (1% CO2, 60% relative humidity, up to 28 day carbonation) using XRD, FTIR and 29Si, 27Al, and 23Na MAS NMR. Samples wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…This indicates the formation of highly cross-linked aluminosilicates upon carbonation. The structural changes in C-A-S-H gel to higher cross-linked aluminosilicates are previously observed [ 24 , 31 , 45 ].…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…This indicates the formation of highly cross-linked aluminosilicates upon carbonation. The structural changes in C-A-S-H gel to higher cross-linked aluminosilicates are previously observed [ 24 , 31 , 45 ].…”
Section: Resultsmentioning
confidence: 75%
“…The CaCO 3 thus formed acts as a diffusion barrier inhibiting the further ingress of CO 2 and carbonation [ 20 ]. Alkali-activated slag systems, unlike PC, do not have Ca(OH) 2 and hence decalcification directly happens in C-S-H [ 20 , 30 , 31 ]. The disparate carbonation mechanism involved in PC and AAS has exacted the AAS to become more vulnerable to carbonation.…”
Section: Introductionmentioning
confidence: 99%
“…Such a correlation is presented in Figure 10. In another study, the depth of carbonation of slag geopolymer paste, tested with phenolphthalein solution, increased with longer carbonation duration [29].…”
Section: Phmentioning
confidence: 94%
“…This process led to a weakening of the sample matrix. On the effect of water content on the properties of a carbon-cured, slag-based, alkali-activated material, it was found that the water-to-binder ratio had a limited impact on the microstructure before and after carbonation, as well as on the formation of carbonates [29]. Moreover, Jun et al [30] developed a carbonation-cured, slag-based geopolymer material suitable for salty and humid environments, where samples achieved most of its strength after 3 days of carbonation curing.…”
Section: Introductionmentioning
confidence: 99%